ASUHAN KEBIDANAN PADA IBU BERSALIN NY X DENGAN MENERAPKAN ASUHAN SAYANG IBU DI PUSKESMAS TANJUNG BALAI KARIMUN - Qurnia, Muti; Susanti, Susanti; Ribut Sulistiyawati, Tri (Universitas Batam, 2024)
Childbirth is an event that ends with the expulsion of a full-term baby, psychological changes, namely feeling afraid that if there is danger to themselves during childbirth, fear that is related to past experiences, for example experiencing difficulties in past deliveries (Rinata, 2018), , if the mother is not enthusiastic or experiences excessive fear, it will make the delivery process difficult. The aim is to provide midwifery care for mothers in a comprehensive and sustainable manner, with management of midwifery care in accordance with midwifery service standards. The midwifery care that was implemented was Midwifery Care for Mrs. X by Implementing Maternal Care. The practice report preparation method was descriptive research using the case study method. The research was conducted at the Tanjung Balai Karimun Health Center in March 2023. The subjects used in case studies with management this midwifery care is Mrs. X. Results and conclusions Evaluation of the care provided related to the Implementation of Midwifery Care for Mothers in Birth Mrs. X By implementing Mother-loving Care can increase mother's confidence in facing the birth process